Intervention and prevention programmes on cyberbullying: A review - Mc Guckin, Conor (Springer International, 2016)
In this ever-changing society, the socio-developmental context that our children and young people encounter is monumentally different from the personal experience of childhood that we experienced. Whilst we can look back with a nostalgic lens at our slow-paced “analogue” world, the emerging digital world is both full of wonderment and full of trickery for our young citizens. As appropriate adults, we are charged with the simultaneous task of encouraging and nurturing inquisitive minds, whilst also engendering them with appropriate life-wide coping skills. In this chapter, we explore the current and emerging knowledge regarding how to prevent cyberbullying incidents, or when they do happen, how we can best consider and respond to the subsequent sequel of events. Rather than present an exhaustive and descriptive review of available prevention and intervention programs, we approach the topic more pragmatically, offering the reader a critical perspective on this emerging and evolving area of societal concern. As colleagues, we seek to recognise your individual and professional knowledge and to supplement this with an approach that seeks to point out where to look but not what to see.
Cyberbullying across the globe: Gender, family and mental health.
Keywords: Prevention; Intervention; Cyberbullying; Review; Victim; Bully; Inclusive Society; ANTI-BULLYING POLICY; BULLY; BULLY-VICTIM; BULLY/VICTIM PROBLEMS; BULLYING; Bullying; Bullying; Bullying, Harassment and Violence in School & the Workplace; Cyberbullying; EDUCATION; School Bullying; Traditional Bullying; prevention of bullying; Children; Education; Gender; Youth